Chronic hepatitis caused by hepatitis C virus showing a discrepancy between serogroup and genotype because of intergenotypic 2b/1b recombination: A pitfall in antiviral therapy with direct‐acting antivirals. Issue 3 (25th September 2017) - Kurata, Hayato; Uchida, Yoshihito; Kouyama, Jun‐Ichi; Naiki, Kayoko; Nakazawa, Manabu; Ando, Satsuki; Nakao, Masamitsu; Motoya, Daisuke; Sugawara, Kayoko; Inao, Mie; Imai, Yukinori; Nakayama, Nobuaki; et al.
Abstract : A 40‐year‐old male patient with virologic relapse after daclatasvir plus asunaprevir therapy for a serogroup 1 hepatitis C virus (HCV) infection visited our hospital for retreatment. Virologic examinations revealed that a genotype 2b HCV strain carrying both NS3‐S122N / D168A and NA5A‐R30Q / L31M / Q54H / Y93H mutations had relapsed. The patient received sofosbuvir plus ribavirin therapy, but virologic relapse occurred once again. Sequencing of the HCV genome clarified an intergenotypic recombination of 2b and 1b with an estimated crossover point between nucleotides 3114 and 3115, corresponding to the N‐terminal end of the NS3 region (DDBJ/EMBL/GenBank databases accession no. LC273304). The NS5B‐S282T mutation was not detected in the HCV strain, and resistance‐association substitutions in the NS3 and NS5A regions were similar to those at baseline. Direct sequencing of the core and NS4A regions corresponding to the targeting sites of genotyping and serogrouping, respectively, is useful to determine the combination of direct‐acting antivirals when a discrepancy is observed between the serogroup and genotype of HCV strains.